Wujud Karakter Pelajar Pancasila dalam 66 Kisah Kebaikan untuk Anak - Citraningrum Dina Merdeka; Mohamad Afrizal; Rofiatul Hima (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study describes the character form of Pancasila students in the text entitled "66 Stories of Kindness for Children." Furthermore, the type of research is qualitative with descriptive method. Words, phrases, or sentences that contain the character form of Pancasila students in "66 Stories of Kindness for Children" are the data of this research. Furthermore, the listening and note-taking technique is the method of collecting data in this study. This study uses a qualitative research type, using a descriptive approach. The results of the study show that in "66 Stories of Kindness for Children" there are characters of Pancasila students. The characters of the Pancasila students found were: (a) faith, fear of God Almighty, and noble character, (b) global diversity, (c) working together, (d) independent, (e) critical reasoning, and (f) creative. The characters of Pancasila students often found in this study are faith, fear of God Almighty, and noble character. Therefore, it can be concluded that the text in "66 Stories of Kindness for Children" is worthy of being used as a reference for learning and the stories in the text have the character values of Pancasila students who are very inspiring in the progress of the nation.